Synthesis and preparation of biobased benzoxazine/bismaleimide copolymers: Thermal, mechanical and dielectric properties. (5th October 2022) - Sha, Xin-Long; Wang, Changze; Tan, Lu; Zhou, Jin; Liu, Zongtang; Fei, Zhenghao; Miao, Jia-Tao
Graphical abstract: A low dielectric constant biobased benzoxazine/bismaleimide copolymer is developed with a green synthesis strategy. Highlights: A unique benzoxazine monomers (E-dea ) with active allyl terminations were synthesized using a green synthesis strategy. Poly(E-dea/BMI) have outstanding thermal, mechanical and low dielectric performances. The nature behind these attractive performances of poly(E-dea/BMI) was intensively investigated. Abstract: Preparation of low dielectric thermosetting resins by green method is a challenging subject. Herein, unique bio-based benzoxazine monomer E-dea was prepared by a solvent-free method using eugenol as phenol source, and then E-dea and bismaleimide (BMI) were copolymerized to prepare poly(E-dea/BMI-0.86) and poly(E-dea/BMI-1) . The comprehensive properties including thermal, mechanical and dielectric properties of the copolymers were studied. Notably, poly(E-dea/BMI-0.86) and poly(E-dea/BMI-1) exhibit low dielectric properties with dielectric constants of 2.85 and 2.79 at 1 MHz, respectively. Besides, the glass transition temperature ( Tg ), the initial thermal decomposition temperature ( Tdi ) and the flexural strength of poly(E-dea/BMI-0.86) and poly(E-dea/BMI-1) are 167 °C and 169 °C, 333 °C and 321 °C and 115 ± 3.5 MPa and 123 ± 4.9 MPa, respectively. The excellent comprehensive performance is attributed to the interaction between flexible and low dielectric decane segments and rigid oxazine and BMI segments.